Abstracts of the International Conference on Water in the Humid Tropics, Kandy, Sri Lanka, 4 December 2006 - United Nations University; International Water Management Institute (United Nations University, 2006)
A pre-conference to Humid Tropical Ecosystems, 5 -9 December, 2006, Kandy, Sri Lanka, commemorating the 50th anniversary of UNESCO Humid Tropics Programme Organized by United Nations University and the International Water Management Institute.